The relationship between the level of physical activity and lung function - Daswara Djajasasmita; Anastasia Y Triningtyas; Syafarina Afrila (ACTA Medical Health Sciences, 2024)
Physical activity is part of the basic needs of daily life, especially to improve the quality of health. Engaging in physical activity can increase blood flow through the lungs, causing oxygen to diffuse into the pulmonary capillaries with a larger or maximum volume. The purpose of the study was to determine the relationship between the level of physical activity and lung function. This study is a cross-sectional analytic study with a sampling technique of consecutive sampling, using a sample of 60 students of the Faculty of Medicine, Universitas Jenderal Achmad Yani who meet the inclusion and exclusion criteria. Research data were obtained using the International Physical Activity Questionnaire (IPAQ)-lf questionnaire instrument to assess physical activity levels and a vitalograph spirometer to assess FVC, FEV1 and FEV1/FVC. Data were analyzed using the Spearmann Rho Correlation Test. The results showed that there was a significant relationship between physical activity level and FVC% (p=0.008 and r=0.399) and FEV1% (p=0.000 and r=0.501), while there was no significant relationship between physical activity level and FEV1/FVC ratio (p=0.071 and r=0.235). Although there was no significant relationship between physical activity level and FEV1/FVC ratio, there was a positive and unidirectional relationship between physical activity level and all lung function parameters in this study. Physical activity is one factor that has a positive influence on the respiratory system.When done regularly there will be adaptation to the body by increasing ventilation for maximum oxygen uptake and better diffusion capacity, resulting in respiratory efficiency. Therefore, students are expected to do physical activity according to recommendations to achieve health benefits, including increasing lung function parameters such as FVC, FEV1 and FEV1/ FVC ratio. DOI : 10.35990/amhs.v3n1.p40-50 REFERENCES Hasibuan R. Terapi sederhana menekan gejala penyakit degeratif. Jurnal Ilmu Keolahragaan. 2010;8:78. World Health Organization. Global Status Report on Physical Activity 2022. Geneva: CC BY-NC-SA 3.0 IGO; 2022. Direktorat P2PTM, Kemenkes RI. Ayo Bergerak, Lawan Obesitas! Jakarta; 2017. World Health Organization. Global Health Risks: Mortality and Burden of Disease Attributable to Selected Major Risks. WHO Press; 2009. Hutapea MDS, Angliadi E. Perbandingan FEV1 pada mahasiswa yang aktif dan tidak aktif berolahraga. DOI: https://doi.org/10.35790/ecl.v1i1.3299. Zarkasi KA, Ramdzan AR, Ramli NZ. Physical inactivity among medical and non-medical students: a cross sectional study. Universiti Malaysia Sabah; 2015. Available from: https://www.researchgate.net/publication/309476739. Badan Litbangkes, Kemenkes RI. Hasil Utama Riskesdas 2018; 2018. World Health Organization. Physical activity. 2022 [cited 2023 Aug 7]. Available from: https://www.who.int/news-room/fact-sheets/detail/physical-activity. Wicaksono A. Buku Aktivitas Fisik dan Kesehatan. 1st ed. Pontianak: IAIN Pontianak Press; 2020. Available from: https://www.researchgate.net/publication/353605384. IPAQ Group. Guidelines for Data Processing and Analysis of the International Physical Activity Questionnaire (IPAQ) – Short and Long Forms; 2005. Available from: ipaq.ki.se. Pelkonen M, et al. Delaying decline in pulmonary function with physical activity. Am J Respir Crit Care Med. 2003;168(4):494–9. Jakes RW. Physical inactivity and lower FEV1: European Prospective Investigation into Cancer-Norfolk Study. Am J Epidemiol. 2002;156(2):139–47. Gunawan A. Relations between exercising and pulmonary functions of students of Medical Faculty of University of Muhammadiyah Makassar [Skripsi]. Makassar: Universitas Muhammadiyah Makassar; 2017. Bakhtiar A, Sastra Amran W. Faal paru statis. Jurnal Respirasi. 2016;2:91–8. Supit T, Syahruddin E. Level of physical activity and its associations with lung function of medical students. eJKI. 2015;3(1). International Physical Activity Questionnaire - Long Last 7 Days, Self-Administered Format; 2002. Available from: www.ipaq.ki.se. Rafi Faiq A, et al. Gambaran sedentary behaviour dan IMT mahasiswa Fakultas Kedokteran YARSI. Majalah Sainstekes. 2018;5(2):66–73. Syauqy A. Hubungan IMT dengan kebugaran jasmani mahasiswa Kedokteran Unja. JMJ. 2017;5:87–93. Seefeldt V, Malina RM, Clark MA. Factors affecting levels of physical activity in adults. Sports Med. 2002;32(3):143–68. Guyton A. Guyton and Hall Textbook of Medical Physiology. 12th ed. Elsevier; 2011. Sherwood L. Introduction to Human Physiology. 8th ed. Cengage Learning; 2013. Mahdalena N, Ariati A. Pengaruh aktivitas fisik dengan IMT pada mahasiswa FK UISU. Jurnal Kedokteran Ibnu Nafis. 2021;10:188–94. Haryati, et al. Faktor yang mempengaruhi kualitas tidur mahasiswa FK UHO. Jurnal Surya Medika. 2020;5(2). Lie JG, Chris A. Hubungan pengetahuan COVID-19 dengan kecemasan mahasiswa FK Untar. Jurnal Kedokteran dan Kesehatan. 2022;18:104–12. Available from: https://jurnal.umj.ac.id/index.php/JKK. Yunus F. Faal paru dan olahraga. Jurnal Respirologi Indonesia. 1997;17. Rawar D. Faktor yang berhubungan dengan kapasitas vital paru pekerja bengkel las. [Skripsi]. Jakarta: UIN Syarif Hidayatullah; 2010. Prihantini N, Batubara F. Faktor yang mempengaruhi fungsi paru pada mahasiswa FK UKI. Jurnal Ilmiah Widya. 2019;6. Tortora G, Derrickson B. Dasar Anatomi dan Fisiologi. 13th ed. Jakarta: EGC; 2020. Aritonang JP, et al. Aktivitas fisik mahasiswa FK Universitas Mataram saat pandemi COVID-19. eJKI. 2022;10(1). Available from: http://doi.org/10.23886/ejki.10.129.58. Riskawati YK, et al. Aktivitas fisik mahasiswa prodi pendidikan dokter tahun 2–4. Majalah Kesehatan. 2018;5(1):27–32. Riskawati Y, et al. Hubungan aktivitas fisik dengan IMT mahasiswa FK UB. Majalah Kesehatan. 2020;7. Habut MY, et al. Hubungan IMT dan aktivitas fisik terhadap keseimbangan dinamis mahasiswa FK Udayana. Majalah Ilmiah Fisioterapi Indonesia. 2015;1:45–51. Makmun A, Pratama A. Gambaran IMT mahasiswa. Indonesian Journal of Health. 2021;2:1–7. Chendra S, Lontoh SO. Hubungan olahraga dengan kapasitas vital paru mahasiswa FK Untar. Tarumanagara Medical Journal. 2019;1(3):643–6. Lamtiar RR, Siallagan F. Korelasi IMT dengan kapasitas vital paksa paru. NJM. 2019;5(1). Available from: http://apps.who.int/bmi/index.jsp?introPage=intro_3.html. Tipa EW, et al. Hubungan kebiasaan merokok dengan kapasitas vital paru penambang emas. Jurnal KESMAS. 2021;10. Azmi NA, et al. Correlation of physical activity with physical fitness and respiratory function in undergraduates. Trends in Sciences. 2021;18(19). Purnama TD, et al. Correlation between physical activity, aerobic capacity, and BMI with lung capacity in adolescence. In: Scitepress; 2020. p. 115–8. Sayed Khashaba A. Effect of physical activity levels on pulmonary function in male Saudi students. Int J Sports Sci. 2015;5:209–12. Available from: https://www.researchgate.net/publication/328654439. Laksono H, et al. Hubungan obesitas dan kebiasaan olahraga dengan kapasitas paru mahasiswa Poltekkes Kemenkes Bengkulu. JNPH. 2019;7(1). Pasek M, et al. Hubungan antara rutinitas olahraga dengan fungsi paru pada perokok muda. JULY. 2020;9(7). Available from: https://ojs.unud.ac.id/index.php/eum. Angane E, Navare A. Effects of aerobic exercise on pulmonary function in healthy adults. Int J Res Med Sci. 2016;6:2059–63.